Diagnosis of pulmonary tuberculosis and assessment of treatment response through analyses of volatile compound patterns in exhaled breath samples. Issue 4 (April 2017) - Zetola, Nicola M.; Modongo, Chawangwa; Matsiri, Ogopotse; Tamuhla, Tsaone; Mbongwe, Bontle; Matlhagela, Keikantse; Sepako, Enoch; Catini, Alexandro; Sirugo, Giorgio; Martinelli, Eugenio; Paolesse, Roberto; Di Natale, Corrado
Summary: Objectives: We determined the performance of a sensor array (an electronic nose) made of 8 metalloporphyrins coated quartz microbalances sensors for the diagnosis and prognosis of pulmonary tuberculosis (TB) using exhaled breath samples. Methods: TB cases and healthy controls were prospectively enrolled. Signals from volatile organic compounds (VOCs) in breath samples were measured at days 0, 2, 7, 14, and 30 of TB therapy and correlated with clinical and microbiological measurements. Results: Fifty one pulmonary TB cases and 20 healthy HIV-uninfected controls were enrolled in the study. 31 (61%) of the 51 pulmonary TB cases were coinfected with HIV. At day 0 (before TB treatment initiation) the sensitivity of our device was estimated at 94.1% (95% confidence interval [CI], 83.8–98.8%) and specificity was 90.0% (95% CI, 68.3–98.8%) for distinguishing TB cases from controls. Time-dependent changes in the breath signals were identified as time on TB treatment progressed. Time-dependent signal changes were more pronounced among HIV-uninfected patients. Conclusion: The identification of VOCs' signals in breath samples using a sensor array achieved high sensitivity and specificity for the diagnosis of TB and allowed following signal changes during TB treatment. Highlights: Analysis of volatile organic compounds (VOCs) in breath samples using sensor technology (electronic nose) is a promising non-invasive approach for the diagnosis and prognosis of pulmonary tuberculosis (TB). In this proof-of-concept study, our electronic nose showed high performance differentiating cases with pulmonary TB from healthy controls. Serial measurements of VOCs also allowed for determining VOC signals change during TB treatment among patients with pulmonary TB. The sensors used in our study are stable enough to allow for longer, larger-scale studies of different designs looking into the diagnostic and prognostic value of VOC analysis for the diagnosis and prognosis of pulmonary TB.